(3Ndb GdEfSGfs - (3CHh SYjO YHO Gdedc Hf bQjH GdGUeYjs
(3ChdgG (B:s
(3bGd CHh SYjO YHO Gdedc Hf bQjH GdCUeYi GdHGgdi (B: (3jbGd ddeQCI ai Chd eG JMed (B: (3bO fSFJ s
(3BNQgG (B:s
(3hai GdQLd (B:" (3GdYQL hGdbRd hYQL jYQL YQLkG (B: (3EPG eTi eTjI GdYQLGf Je GdcJGH HMeO Gddg hYhfg s
(3jdi GdeNWhW hQbJGf ef cJGH fYhJ GdfSGA ddCUeYis
(3Ke ChQGb ef cJGH Ndb GdEfSGf hVYJ ai ZjQ ehVhYgGs
(3hQbJGf ai eYfi GdTghQ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs